Entrepreneurship as a viable solution for unemployed graduates: an overview of South African unemployed graduates - Mabunda, N (Faculty of management and law international Conference (FMLIC), 2024)
The rising number of unemployed graduates in South Africa is a significant socio-economic challenge, with traditional job markets failing to absorb the growing educated workforce. This paper explores entrepreneurship as a viable solution for unemployed graduates, examining its potential to create sustainable employment opportunities and drive economic growth. The study delves into the current state of unemployed graduate in South Africa, identify key challenges for graduate contemplating entrepreneurship initiatives, the benefit of entrepreneurship for unemployed graduate. It further investigates the skills and competencies required for successful entrepreneurship as well as the support mechanism for South African graduates in entrepreneurship. To achieve the objective of this paper, the author made use of existing literature, journals and books, government documents and internet sources. Through a comprehensive review of literature, the paper highlights successful entrepreneurial initiatives and support mechanisms in1 South Africa. The findings suggest that with appropriate training, mentorship, and access to funding, entrepreneurship can be a compelling alternative for unemployed graduates, fostering innovation and economic resilience. Furthermore, the paper concludes by recommending the strategic interventions to promote entrepreneurial activities among South African graduates, ultimately contributing to a reduction in unemployment rates and a more dynamic economy. The researcher suggests further research on entrepreneurship and unemployed graduates, which could offer valuable insights to policymakers, educators, and financial institutions, thereby creating a more supportive environment for unemployed graduates to thrive.
Journal article of FMLIC - Conference Proceedings 2024
Keywords: Entrepreneurship; Unemployment; Graduates; Economic Growth; Unemployment; Economic development.